Recent developments in maintaining gel properties of surimi products under reduced salt conditions and use of additives. Issue 30 (7th November 2022) - Monto, Abdul Razak; Li, Mengzhe; Wang, Xin; Wijaya, Ganesha Yanuar Arief; Shi, Tong; Xiong, Zhiyu; Yuan, Li; Jin, Wengang; Li, Jianrong; Gao, Ruichang
Abstract: Salt is a necessary condition to produce a surimi product that is based on the gelation of salt-soluble myofibrillar proteins. Recently, there has been a growing concern among consumers to consume healthy foods due to the threat of several chronic diseases caused by an unhealthy diet. Methods of reducing salt content out of concern for health issues caused by excessive sodium intake may affect the gel properties of surimi, as can many health-oriented food additives. Several studies have investigated different strategies to improve the health characteristics of surimi products without decreasing gel properties. This review reports recent developments in this area and how the gel properties were successfully maintained under reduced-salt conditions and the use of additives. This review of recent studies presents a great deal of progress made in the health benefits of surimi and can be used as a reference for further development in the surimi product processing industry. Graphical Abstract: UF0001